Epidemiology and Risk Factors for Thromboembolic Complications of Childhood Nephrotic Syndrome: A Midwest Pediatric Nephrology Consortium (MWPNC) Study - Kerlin, Bryce A. (2009)
OBJECTIVES: To identify clinical variables predictive of the risk of thromboembolism (TE), and to confirm the incidence of TE in primary and secondary childhood nephrotic syndrome (NS). STUDY DESIGN: A comprehensive chart review identified 326 children with NS from any cause evaluated between 1999 and 2006. These patients had a total of 1472.8 patient-years of follow-up. Comparison statistics, survival analysis, and logistic regression were used to define TE epidemiology and clinical risk factors. RESULTS: We found that 9.2% of our cohort had experienced at least 1 TE. The overall incidence was 20.4 patients with TEs/1000 patient-years. The median time to the first TE was 70.5 days after diagnosis of NS. Deep venous thrombosis was the most common TE (76%) and was frequently associated with the use of a central venous catheter (45%). Significant independent predictors of TE included age ≥ 12 years at onset of NS (P < .0001), severity of proteinuria (P < .0001), and history of TE preceding diagnosis of NS (P < .0001). Life- or limb-threatening TEs represented 23.7% of the events. CONCLUSIONS: Children with NS should be carefully followed for TE, particularly those who are age 12 years or older, have severe proteinuria, or have a previous history of TE.